PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA KINERJA PEGAWAI LPD DI KECAMATAN MENGWI MELALUI MOTIVASI KERJA - Ida Ayu Mas Agung Prama Iswari; Ni Made Yuli Kartika Dewi; Bagus Arya Kusuma; Ni Putu Sudarsani; I Wayan Terimajaya (Jurnal Ilmiah Satyagraha, 2026)
ABSTRACT   This study aims to determine: 1) the direct influence of leadership, work environment, and work motivation on the performance of LPD employees in Mengwi District, Badung Regency. 2) the direct influence of leadership and work environment on the work motivation of LPD employees in Mengwi District, Badung Regency. 3) the indirect influence of leadership and work environment on the performance of LPD employees in Mengwi District, Badung Regency through work motivation. This study took a sample of 105 respondents, the analysis technique used in this study is path analysis. The results of the study indicate that 1) there is a direct positive and significant influence of leadership, work environment, and work motivation on the performance of LPD employees in Mengwi District, Badung Regency. 2) There is a direct positive and significant influence of leadership and work environment on the work motivation of LPD employees in Mengwi District, Badung Regency. 3) There is an indirect influence of leadership and work environment on the performance of LPD employees in Mengwi District, Badung Regency through work motivation.